Study on numerical solution of dispersive water wave phenomena by using a reliable modification of variational iteration algorithm - Ahmad, Hijaz; Seadawy, Aly R.; Khan, Tufail A. (Mathematics and computers in simulation, 2020)
In this paper, we propose an incredible modification of variational iteration algorithm-II that will accelerate the fast convergence of the series solution. We utilize the proposed algorithm on KdV, mKdV and combined KdV–mKdV equations to illustrate its accuracy and reliability. The consequences of modified variational iteration algorithm-II (MVIA-II) show that the proposed technique minimizes the size of calculations, converges rapidly, computationally efficient and yields accurate results. This modification demonstrated the high efficiency and attained very good agreement in illustrated models and might be promptly reached out to other nonlinear PDEs.